Efforts to Implement Hindu Religious Learning For students at SD Negeri 1 Menteng - Rusdini; Mitro; I Gede Dharman Gunawan (IAHN-TP Palangka Raya, 2024)
There are still many Hindu students who have bad attitudes and behavior, such as being polite towards teachers and friends at school, so Hindu religious learning is implemented so that Hindu students have good character. The efforts of Hindu religious education teachers to implement Hindu religious learning for students at SD Negeri 1 Menteng Palangka Raya are efforts to provide learning for students to provide the values ??of Hindu religious teachings such as tat twam asi, efforts to provide assignments for Hindu students to familiarize students with having an attitude of responsibility. Efforts to practice Hindu religious events for students to deepen good religious, moral and ethical values.